2021
DOI: 10.1186/s13071-020-04560-x
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the impact of outdoor vector control interventions on malaria transmission intensity from semi-field studies

Abstract: Background Semi-field experiments with human landing catch (HLC) measure as the outcome are an important step in the development of novel vector control interventions against outdoor transmission of malaria since they provide good estimates of personal protection. However, it is often infeasible to determine whether the reduction in HLC counts is due to mosquito mortality or repellency, especially considering that spatial repellents based on volatile pyrethroids might induce both. Due to the va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
73
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(74 citation statements)
references
References 40 publications
0
73
1
Order By: Relevance
“…There is no need for complete eave screens as treated fabric strips will be sufficient and can provide a simple, easy-to-handle tool for protecting people from infectious bites. However, the climatic conditions under which such a tool provides optimum protection must be investigated further and potentially incorporated into mathematical modelling approaches [ 66 ] to provide essential guidance on where and when to target this intervention. Field studies need to confirm these findings under more variable natural conditions and need to determine the range and longevity of the spatial repellent effects.…”
Section: Discussionmentioning
confidence: 99%
“…There is no need for complete eave screens as treated fabric strips will be sufficient and can provide a simple, easy-to-handle tool for protecting people from infectious bites. However, the climatic conditions under which such a tool provides optimum protection must be investigated further and potentially incorporated into mathematical modelling approaches [ 66 ] to provide essential guidance on where and when to target this intervention. Field studies need to confirm these findings under more variable natural conditions and need to determine the range and longevity of the spatial repellent effects.…”
Section: Discussionmentioning
confidence: 99%
“…commun.). Though there has not been large-scale epidemiological trials, experimental studies and mathematical models have shown efficacy of transfluthrin-treated eave ribbons to reduce biting both indoors and outdoors, and potential to disrupt overall malaria transmission [ 49 ]. Table 1 summarises the studies on eave ribbons.…”
Section: Introductionmentioning
confidence: 99%
“…Hence eave ribbons have potential in managing insecticide resistance Masalu et al [ 45 ] 10 Predicting the impact of outdoor vector control interventions on malaria transmission intensity from semi-field studies Statistical modelling of semi field eave ribbons data from Tanzania and Kenya Laboratory-reared Anopheles arabiensis 41–96% Transfluthrin treated eave ribbons provide both personal and community protection. Denz et al [ 49 ] 11 Transfluthrin Eave-Positioned Targeted Insecticide (EPTI) Reduces Human Landing Rate of Pyrethroid Resistant and Susceptible Malaria Vectors in a Semi Field Simulated Peri-domestic Space Eave ribbons were treated following the procedures described by Mmbando et al [ 37 ] Laboratory-reared Anopheles arabiensis 80% 68% Transfluthrin treated eave ribbons have potential tackle the challenges of insecticide resistance in malaria vectors Tambwe et al [ 56 ] 12 Evaluating putative repellent ‘push’ and attractive ‘pull’ components for manipulating the odour orientation of host-seeking malaria vectors in the peri-domestic space Hessian strip [21 m × 0.05 cm] impregnated with 10 ml technical grade transfluthrin prepared in soapy water; the strips suspended overnight indoors to dry Tests were done in large semi-field cage Laboratory-reared Anopheles arabiensis Not assessed 94% Transfluthrin treated hessian fabric strips around eave gaps provide significant protection from mosquito bites in the peri-domestic spaces. Njoroge et al [ 57 ] The table focuses primarily on hessian-based eave ribbons and excludes other eave-based technologies …”
Section: Introductionmentioning
confidence: 99%
“…Additional studies have shown that the success of ERB assays depends on the procedural ease for introducing and removing female mosquitoes in a semi-field system which is “ideally situated within the natural ecosystem of the target disease vector and exposed to ambient environmental conditions, within which all features necessary for its lifecycle completion are present” [ 5 , 9 – 11 ]. These limitations may account for the lack of precise estimates of the value and variability of the repelling effect of any product inhibiting outdoor biting versus its killing and disarming (preventing host-seeking until the next night) effects based on human landing collection data obtained from controlled Semi-Field System (SFS) experiments [ 12 ]. Clearly, to assess the effectiveness of candidate tools in an early stage of product development, intermediary testing grounds between the laboratory and field within disease-endemic countries are needed to fight outdoor malaria transmission and Aedes -borne viral diseases [ 13 ].…”
Section: Introductionmentioning
confidence: 99%